Effect Determination of Kaaraman Ko, Iwaras Ko: A Community Extension Program - Ronnie Rubi (Philippine Association of Institutions for Research, Inc., 2019)
Kaaraman Ko, Iwaras Ko is a community-based technology education extended by the college anchored to the CMO 52 s. 2016. This study is an assessment of the aforementioned program. Kaaraman Ko, Iwaras Ko was aimed to educate and capacitate the beneficiaries with applied technology skills in (a) food processing, bread, and pastry production, (b) garment technology and (c) household wiring and electrical installation. The study determined the effect of the program on the beneficiaries' personal development, on the beneficiaries' adoption of the skills they acquired from the training, and on augmenting the family income of the beneficiaries. Mixed-method of research was utilized in the study. Surveys and focus group discussion (FGD) was used to collect data. Results show that of the 70 beneficiaries that adopted the skills they learned from the program, four (4) started a small business, eleven (11) used the skills they learned to seek employment and fifty-five (55) applied it at home or in personal use. On average, the participants agree (3.52) that the program has helped them to have a better personality development and they also agree (3.29) that their stress was reduced. The participants strongly agree (3.51) that the program has helped increase their family's income.